2018
DOI: 10.37358/mp.18.4.5104
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Using the Sewage Sludge in Agriculture in Romania

Abstract: Sewage sludge resulted from urban wastewater treatment plants is generally accepted as a valuable source of nutrient and soil conditioner for agricultural usage. Analysis of amount of heavy metals in sewage sludge is essential previous to utilization of the sludge to agriculture considering the inevitable risk of heavy metal toxicity to soil, vegetation and humans. The present paper aims to analyse the characteristics of the sewage sludge resulted in an urban area for 5 years. Sewage sludge generated from five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In general, sewage sludge produced in Romania contains heavy metals, but far below the maximum limit allowed for use in agriculture. Balanica et al, 2018 [ 19 ] showed that the content of heavy metals in sludge from five sewage treatment plants from South of Romania Giurgiu, Calarasi, Braila, Galati and Tulcea is below the maximum allowed limit. Ailincai et al, 2012 [ 20 ] showed that the two-year application of 30 t/ha of sludge from the sewage treatment plant in Iasi on an arable land in the Moldavian Plateau contributed to an improvement in soil properties through an increase in the organic carbon content from soil by 4.6 g/kg (28%), compared to the unfertilized variant.…”
Section: Discussionmentioning
confidence: 99%
“…In general, sewage sludge produced in Romania contains heavy metals, but far below the maximum limit allowed for use in agriculture. Balanica et al, 2018 [ 19 ] showed that the content of heavy metals in sludge from five sewage treatment plants from South of Romania Giurgiu, Calarasi, Braila, Galati and Tulcea is below the maximum allowed limit. Ailincai et al, 2012 [ 20 ] showed that the two-year application of 30 t/ha of sludge from the sewage treatment plant in Iasi on an arable land in the Moldavian Plateau contributed to an improvement in soil properties through an increase in the organic carbon content from soil by 4.6 g/kg (28%), compared to the unfertilized variant.…”
Section: Discussionmentioning
confidence: 99%
“…However, sewage sludge could contain toxic chemicals for the environment. Experimental analysis of heavy metals' concentration in sewage sludge resulting from Galati urban WWTPs showed values below national limits [65]. Such investigations are necessary to detect and monitor potential risks associated with agriculture applications.…”
Section: Sustainable Wastewater Treatment Facilities and Water Resource Usagementioning
confidence: 99%
“…Therefore, their chemistry and composition determine the potential usage of the sludge or disposal prerequisites (Praspaliauskas & Pedisius, 2017). The sewage sludge collected from non-industrial hinterlands can be recycled back to the agricultural lands more safely in terms of heavy metal contaminants and can be treated as valuable sources of plant nutrients and soil conditioner (Balanica et al, 2018;Sharma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%